Success of Georgia Extension PSAs - Joe Courson (Journal of Applied Communications, 1988)
Evaluation! We hear the term more and more in extension service work and it's no different with radio programming. In Georgia, we wanted to know if the resources spent on agricultural public service announcements (PSAs) for radio were worth it.